Evaluation of the influence of recombinant human tumor necrosis factor on adhesive ability of human fetal umbilical vein endothelial cells to К562 and L1210 cells - Barilka, V.A.; Matlan, V.L.; Prymak, S.V.; Loginsky, V.Y. (Experimental Oncology, 2013)
Regulation of adhesion receptors (AR) expression on endothelial cells (EC) is controlled by tumor necrosis factor (TNF), a pleiotropic cytokine, being a local mediator of cellular homeostasis and immune response. TNF is one of the first cytokines that are secreted in inflammation and lymphoid tumors (LT). The increase in TNF-α expression promotes tumour metastasis and induces the endothelial dysfunction in many pathophysiological conditions. Aim of study was to determine an adhesive ability of human fetal umbilical vein endothelial cells (НUVECs) to adhere to cells of leukemic lines К562 and L1210 after treatment with various concentrations of recombinant human TNF (rhTNF), (Sigma, USA). Materials and Methods: HUVECs were obtained as described Jaffe E.A. et al., 1973. Cell suspension of К562 or L1210 were labeled with 3H-thymidine but not activated with rhTNF before experiment and were added to the monolayer of HUVECs. The level of attachment cells was estimated as the index of adhesion (IA). Doses of rhTNF were selected according to the predefined blood level of endogenous TNF in healthy subjects and patients with hematologic diseases and have been divided into low, intermediate, high and stimulating ones (the concentration range of 0.001–6.946 ng/ml). HUVECs that were incubated in a non-rhTNF medium have been used as controls. Results: rhTNF exerted a complex dose-dependent influence on adhesive properties of HUVECs in vitro. Parameters of AI for the К562 and L1210 cells were related to the morphologic type of cell line, which was evidenced by a high statistical correlation. Cells L1210 were characterized by high IA parameters after their treatment with low or stimulating doses of rhTNF. Cells К562 adhered to HUVECs after their treatment with stimulating doses of rhTNF. Conclusion: As proven by the obtained results, the TNF cytokine-activated vascular endothelium plays a pivotal role in the initiation of adhesion, while the influence of autocrine secretion of TNF in the very moment of the formation of intercellular contacts.